A Study on Fuzzy Ideals of N-Groups. (26th September 2013) - Davvaz, B.; Ratnabala Devi, O.
Abstract : Using the idea of the new sort of fuzzy subnear-ring of a near-ring, fuzzy subgroups, and their generalizations defined by various researchers, we try to introduce the notion of (ϵ, ϵ ∨ q )-fuzzy ideals of N -groups. These fuzzy ideals are characterized by their level ideals, and some other related properties are investigated.